Structural performance of bamboo sandwich panel (BSP) with openings as load bearing wall - Nor Hidayah Shafiai,; Rohana Hassan,; Mohd Hanizan Bahar,; Anizahyati Alisibramulisi,; Ali Awaludin,; Ahmad Mazlan Othman, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Studies on utilizing bamboo as structural and strengthening components still need to be completed. This paper presents a case study on effective and practical approaches for bamboo sandwich panels (BSP) designed as load-bearing walls with and without openings that can withstand heavy weights. Three specimens for each type of wall, all with a height of 1200mm and a width of 600mm, were tested. The BSP walls without openings were tested and considered as control specimens. The BSP walls were constructed with a square opening of 150 x 150 mm at the centre of the panel. The compression and moisture content properties of small clear bamboo materials made of Bambusa Vulgaris species were also measured. The test results show the effectiveness of BSP as a strengthening material to reinforce load-bearing walls with significant stiffness and ultimate bearing load. The BSP with an opening has reduced 31.76% of the wall load-carrying capacity compared to the wall without an opening. The study’s findings on BSP offer promising applications in various construction and architectural contexts. The significant stiffness and ultimate bearing load demonstrated by BSPs suggest their potential as sustainable alternatives to conventional load-bearing materials.